T-cell activation by autologous human T-cell leukemia virus type I-infected T-cell clones. - Wucherpfennig, K W (1992)
A unique feature of both human T-cell leukemia virus type I (HTLV-I) carriers and subjects with HTLV-I-associated myelopathy/tropical spastic paraparesis (HAM/TSP), a chronic inflammatory disease of the nervous system, is the presence of large numbers of activated T cells that spontaneously proliferate in vitro. We have investigated the mechanisms of T-cell activation by HTLV-I in freshly isolated blood T cells and in naturally infected T-cell clones obtained by direct single-cell cloning from patients with HAM/TSP. Both CD4+ and CD8+ HTLV-I-infected T-cell clones showed the unusual ability to proliferate in the absence of exogenous interleukin 2 (IL-2). Nevertheless, HTLV-I-infected clones were not transformed, as they required periodic restimulation with phytohemagglutinin and feeder cells for long-term growth. Irradiated or fixed HTLV-I-infected clones were found to induce the proliferation of blood T cells when cocultured, which we refer to as THTLV-1-T cell activation. This THTLV-1-T cell-mediated activation was blocked by monoclonal antibodies (mAbs) against CD2/lymphocyte function-associated molecule 3 (LFA-3), LFA-1/intercellular cell-adhesion molecule (ICAM), and the IL-2 receptor but not by mAbs against class I or class II major histocompatibility complex molecules, HTLV-I gp46, or a high-titer HAM/TSP serum. Spontaneous proliferation of blood T cells from HAM/TSP patients could also be inhibited by mAbs to CD2/LFA-3, LFA-1/ICAM and to the IL-2 receptor (CD25). These results show at the clonal level that HTLV-I infection induces T-cell activation and that such activated T cells can in turn stimulate noninfected T cells by cognate THTLV-1-T cell interactions involving the CD2 pathway.